Deconstructing international politics - Dillon, Michael, 1945- (Milton Park, Abingdon, Oxon ; New York : Routledge, 2013)
"This book is the first full length manuscript to draw on the the insights and techniques of deconstruction to analyse international relations. Influenced primarily by Derrida, it critiques the cornerstones of international relations such as modernity, the state, the subject, security and ethics and justice"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: International relations; International relations -- Philosophy; Electronic books